Determination of fatigue crack growth trajectory and residual life under mixed modes - Blažić, Marija (Strojniški vestnik, 2014)
This paper considers the determination of the crack growth trajectory and residual life for the two-dimensional structural elements under mixed modes. To study crack growth behaviour, a specimen with two holes and a crack between them is considered. This crack is defined as achieving a mixed-mode I/II crack growth trajectory. To produce a crack growth trajectory under cyclic loads with an initial crack between the two holes, MTS servo-hydraulic system is used. Crack growth trajectory is defined using numerical simulations via finite elements. The results of the numerical simulations by finite elements are compared with experimental results. Residual life along the "curve" mixed-mode crack growth trajectory is determined numerically and experimentally. The crack growth trajectory obtained via the presented numerical simulation and residual life are compared with own experimental results.
Keywords: ocenjevanje preostale dobe uporabnosti; rast utrujenostne razpoke; simulacije metod končnih elementov